EMPOWERMENT OF WOMEN'S ECONOMY SUPPORTING THE ACHIEVEMENT OF GENDER EMPOWERMENT IN NORTH KALIMANTAN - Renta Yustie; Ermatry Hariani; Billy Fernando; Nuri Nur Azizah (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The issue of gender empowerment is very important to discuss. This research discusses the equality of women and men in terms of economy and professional work, which is a priority in North Kalimantan. Using data from the Indonesian central statistics agency and using statistical testing tools. This research is a quantitative study using panel data methods. The research sample uses 5 (five) districts/cities in North Kalimantan Province, namely Malinau Regency, Bulungan Regency, Tana Tidung Regency, Nunukan Regency, and Tarakan City. The purpose of this research gap is to examine what factors influence the gender empowerment index and on the other hand, the involvement or role of women in North Kalimantan, which is low in terms of economic aspects. Research results show that the variable of women's income contribution (SPP) has a significant effect on the gender empowerment index (IDG).